The Effectiveness of Schoology-Assisted PBL-STEM to Improve Critical Thinking Ability of Junior High School Students - Febrianto, Taufan; Ngabekti, Sri; Saptono, Sigit (Universitas Negeri Semarang, 2021)
Current learning tends to use less varied and teacher-centered methods. The selected learning models and approaches have not been able to motivate students to be able to think critically, so that it affects the science scores in general that do not meet the minimum completeness limit The purpose of this study is to analyze the effectiveness of Schoology-assisted PBL-STEM by Environmental Pollution material in increasing critical thinking skills, as well as student learning outcomes. This study was conducted at Junior High School Maria Mediatrix with 4 classes sample, all of which were experimental classes with a total of 114 students. This study is a quantitative study with quasi-experimental study type. To determine the increase in critical thinking skills used the N-gain score test from the pretest and posttest results of four classes in the study that acted as experimental class. The results of the study and analysis can be concluded that critical thinking skills of students who are taught with problem-based virtual learning with STEM approach assisted by Schoology on Environmental Pollution material obtained an average N-gain score of 0.46, in moderate category, so that learning is said to be effective, and an average increase of indicator providing elementary clarification, building basic support and managing strategy and tactics has a higher N-gain score than inference. From learning completeness aspect, there are 94 students who complete individually, 82.5% of the students complete classically. This study can contribute to the development of virtual science learning, especially in the use of PBL-STEM model with better technical implementation.